Whitaker's almanack 2008 - Gale Group (London, England A & C Black Publishers, 2007)
Brings together a wide range of facts, figures and directory information on current affairs and general knowledge. Contains a comprehensive overview of every aspect of United Kingdom infrastructure and an excellent introduction to world politics.
Preface -- The year 2008 -- United Kingdom -- Royal family -- Precedence -- Peerage -- Parliament -- The government and public bodies -- Regional government -- Local government -- European parliament -- Law and order -- Defence -- Education -- Health -- Social welfare -- Utilities and transport -- Religion -- Communications -- Information technology -- The environment -- Heritage -- Banking and finance -- Legal notes -- The media -- Organisations -- The world -- The year 2006-7 -- Time and space -- General reference -- Abbreviations -- Index -- Stop press.
Electronic reproduction.
Keywords: Almanacs, English; Great Britain -- Statistics; Great Britain -- Commerce; Great Britain -- Politics and government; Great Britain -- Civilization; Electronic books